STRATEGI PERCEPATAN PENGEMBANGAN INDUSTRI HILIR KARET DAN KELAPA SAWIT DI SUMATERA SELATAN - BADIA PERIZADE; ANDY MULYANA (Program Studi Magister Manajemen FE Unsri, 2014)
Commodity development of agriculture in the from of primary product in Indonesia which began with the rubber has developed abaout a century, and the relatively recent palm thirty-five years. Most of the primary product are exported to the word market and the price is always fluctuating according supply and demand conditions of the word market this led to foreign exchange earning and income economic actors foreign earnings will only be obtained if downstream industry is developed for both these commodities south Sumatra has a great opportunity to implement the downstream industry on the basis of abundant raw material resources ,the existence of a development plan in the ocean port of Tanjung Api-api, development of transport infrastructure, energy, water, and support a variety of related institutional. Of course the main actor is the both domestic and foreign,either already engaged in the crumb rubber industry as well as other industries.One location is in special economic zone (KEK) near Tanjung Api-api, and most importantly, a strong commitment and cooperation between actors coherent, government ,the public and researchers to realize the development of downstream industries of rubber and palm oil.